Cochlear Implantation Outcomes in Patients With Retrocochlear Pathology: A Systematic Review and Pooled Analysis. Issue 9 (1st October 2022) - Schlacter, Jamie A.; Kay-Rivest, Emily; Nicholson, Joseph; Santacatterina, Michele; Zhang, Yan; Jethanamest, Daniel; Friedmann, David R.; McMenomey, Sean O.; Roland, J. Thomas
Abstract : Objective: To review the current literature regarding cochlear implantation in patients with retrocochlear pathologies and extract speech perception scores between 6 months and 1 year after surgery. Databases Reviewed: PubMed/MEDLINE, Embase and Cochrane CENTRAL via Ovid, CINAHL Complete via Ebsco, and Web of Science. Methods: The review was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Search strategies included keywords and subject headings to maximize retrieval and reflect cochlear implants and retrocochlear pathologies. Patients with previously resected vestibular schwannoma (VS) were excluded. Results: There were 2, 524 abstracts screened against inclusion criteria, and 53 studies were included, with individual data available for 171 adult patients. Pathologies included were either observed or irradiated VS (previously operated tumors were excluded) (n = 99, 57.9%), superficial siderosis (n = 39, 22.8%), neurosarcoidosis (n = 11, 6.4%), and previous central nervous system or skull base radiation (n = 22, 12.9%). Mean (standard deviation) postoperative consonant-nucleus-consonant (CNC) word scores were 45.4% (24.2) for observed VS, 44.4% (20.8) for irradiated VS, 43.6% (21.0) for superficial siderosis, 89.5% (3.0) for neurosarcoidosis, and 30.0% (30.2) in patients with previous central nervous system or skull base irradiation. Irradiated compared with observed VS had similar postoperative CNC word scores (effect size, 0.06; p = 0.71). Age, sex, maximal tumor dimension, and neurofibromatosis type 2 status did not significantly impact cochlear implant performance in patients with VS. Eighty-two percent of patients with reported device usage were daily users, and overall, 82% of cases benefitted from cochlear implantation. Conclusion: Cochlear implantation in patients with concomitant retrocochlear pathology generally results in improved speech discrimination scores sustained over time.